2010
DOI: 10.1517/14656566.2010.496453
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib: a clinical and pharmacologic review

Abstract: Sorafenib is a well-tolerated oral antiangiogenic agent approved for treatment of two angiogenesis-driven cancers. Studies to broaden the clinical indications and increase understanding of the clinical and laboratory biomarkers of response are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(104 citation statements)
references
References 49 publications
0
102
0
2
Order By: Relevance
“…Pharmacological approaches to studying protein kinases can be challenging to implement because it is difficult to generate selective ATP-competitive inhibitors. In several serendipitous cases, an originally unwanted "off target" of a kinase inhibitor in the clinic turned out to drive therapeutic efficacy while the original target was irrelevant (5,6).…”
Section: Chemical Genetics | Irreversible Inhibitor | Sgk494mentioning
confidence: 99%
“…Pharmacological approaches to studying protein kinases can be challenging to implement because it is difficult to generate selective ATP-competitive inhibitors. In several serendipitous cases, an originally unwanted "off target" of a kinase inhibitor in the clinic turned out to drive therapeutic efficacy while the original target was irrelevant (5,6).…”
Section: Chemical Genetics | Irreversible Inhibitor | Sgk494mentioning
confidence: 99%
“…Sorafenib causes apoptosis in leukemia cell lines and in blast cells from patients with acute myeloid leukemia (10) and displays a broad-spectrum antitumor activity in colon, breast and non-small-cell lung cancer xenograft models (11). Sorafenib was approved by the U.S. Food and Drug Administration for the treatment of patients with advanced renal cell carcinoma and unresectable hepatocellular carcinoma (12). As the first drug to improve the survival of patients with hepatocellular carcinoma, sorafenib is currently being tested in clinical trials for its efficacy in the treatment of other solid tumors such as thyroid carcinoma (12).…”
Section: Sorafenib-induced Apoptosis Of Chronic Lymphocytic Leukemia mentioning
confidence: 99%
“…PTK inhibitors with broad-spectrum specificity are increasingly expected to demonstrate a better clinical benefit than selective agents [26] . Some multi-targeted PTK inhibitors approved by the FDA/ EMEA, such as sorafenib [27] and sunitinib [28] , are marked as a new generation of PTK inhibitor drugs. We have previously reported that hematoxylin is a multi-targeted inhibitor of several tyrosine kinases, including c-Src, c-Met, FGFR1, EGFR, VEGFR, PDGFR, and c-Kit [29] .…”
Section: Discussionmentioning
confidence: 99%